The Erythropoietin Receptor: Molecular Structure and Hematopoietic Signaling Pathways - Watowich, Stephanie S. (2011)
The process of erythropoiesis in the fetal liver and adult bone marrow is regulated by the hormone erythropoietin (Epo), which is produced in the kidney at low levels under homeostatic conditions. Defects in Epo production result in severe anemia; use of recombinant hormone has improved the lives of patients suffering from renal failure or anemia due to bone marrow suppression. Deletion of the Epo gene in mice leads to embryonic lethality at day 13–15, coincident with the establishment of definitive (adult-type) erythropoiesis and underscoring the absolute necessity of Epo function in vivo. Epo has proven to be a successful pharmaceutical agent, one of the early triumphs of recombinant protein technology. Due to its clinical importance, a great deal of attention has focused upon the molecular mechanisms of Epo-regulated erythropoiesis. This review highlights basic concepts of Epo signal transduction within the hematopoietic system, the major site of Epo action in vivo.